Comparative Performance Analysis of Gear Oil Enhanced With Biomass-Derived Cellulose Nanocrystals and Al2O3 Nanoparticles - Ahmed Nabhan; Hamouda M. Mousa; Husain Alfadhel; Mohamed R. El-Sharkawy; Hossa F. Al-Shareef; Fatimah A. M. Al-Zahrani; Mohamed Taha (International Journal of Polymer Science)
This investigation conducts a side-by-side assessment of gear oil augmented with a unique hybrid nanoparticle variant: cellulose nanocrystals (CNCs) sourced from biomass and aluminum oxide (Al2O3) nanoparticles (NPs). The objective is to ascertain the impact of these NPs on the lubricative qualities of gear oil which is a critical factor for the peak functioning and durability of mechanical systems. The composite samples were formulated with varying concentrations of a hybrid mixture, consisting of 0.25, 0.5, 0.75, and 1.0 wt.% of CNCs combined with 1.0 wt.% of Al2O3 NPs. The study involved the synthesis and characterization of CNC-Al2O3 NP gear oil composites through various techniques. These techniques include infrared (IR) spectral analysis and X-ray diffraction (XRD), as well as assessments of kinematic viscosity, friction, and wear scar dimensions. The results of the IR analysis reveal that incorporating of Al2O3 NPs and CNCs into engine oil dramatically improves its chemical and physical attributes. The kinematic viscosities of the nano-oil samples grew up to 5.4% and 15.5% with the incorporation of 1.0 wt.% CNCs and 1.0 wt.% Al2O3 NPs at 40°C and 100°C, corresponding to a 16.7% increase in the viscosity index. Moreover, it can be evident that the coefficients of friction (COFs) and wear scar declined up to 26% and 36%, respectively, due to loading content of 0.75 wt.% CNCs and 1.0 wt.% Al2O3 NPs. Therefore, the vibration acceleration response root mean square (RMS) collapsed by up to 28%, and sound levels declined by 11%, indicating that the hybrid nanolubricant has a superior effect.